The Relationship Between Self-Regulated Learning Strategies and Reading Comprehension in Narrative Text - Pratama, Dedy; Purnomo, Hari Agus; Irawan, Candra; Sinaga, Bunga Riama; Almidawati (Journal of English Education, 2023)
The purpose of this study was to determine (1) the student's SRL strategies at SMP N 5 Palembang, and (2) whether or not there was a significant correlation between Self-Regulated Learning Strategies (SRL) and reading comprehension in the narrative text at SMP N 5 Palembang. This study's population and sample were students in the eighth grade at SMP N 5 Palembang. The sample size was 46 students, chosen using a non-random sampling technique. To collect data, students were given a questionnaire about self-regulated learning (SRL) strategies and a reading comprehension test. The data were analysed using correlation analysis. Based on the statistical analysis, the correlation coefficient or R-value (0.631) was found to be greater than R-table (0.245). The significance level (p) (sig.2-tailed) was then 0.000. This indicates that the p-value (0.000) was less than 0.05. It is possible to conclude that there was a highly significant correlation between the students' self-regulated learning strategies and reading comprehension in narrative text.